BIBLIOGRAPHY OF WORKS IN THE FIELD OF TEACHING METHODOLOGY OF SERBIAN AS A FOREIGN LANGUAGE (2018–2022) (Živi jezici: Journal for Foreign Languages and Literatures, 2023)
Taking into account the obvious increase in interest in the methodology of teaching Serbian as a foreign language, our goal is to present with this bibliography published scientific results in the period from the middle of 2018 to the end of 2022, as well as to make data on published monographs and scientific articles as accessible as possible to interested professional public.
Keywords: Serbian as a foreign language; methodology of teaching Serbian as a foreign language; bibliography of papers